1992
DOI: 10.1016/s0022-5347(17)37507-9
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Histopathological Examination Contributes to the Assessment of Escherichia Coli Urovirulence

Abstract: To determine the usefulness of detailed histopathological evaluation in the assessment of urovirulence of different Escherichia coli strains in a mouse model of ascending, unobstructed urinary tract infection, and to evaluate the relationship between susceptibility to urinary tract infection and renal levels of P fimbrial receptor glycolipids in different mouse strains, female Swiss Webster and Balb/c mice were inoculated transurethrally with one of four different well-characterized wild type E. coli strains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Coordinate regulation among fimbrial operons has been described previously and may provide an explanation for this observation (17,44). P fimbriae, argued as being virulence factors during UTI (43), are found downregulated here in vivo despite the presence of P-fimbrial Gal-Gal receptors in mice (22,32). Our microarray experiments suggest that a better way to study the importance of other adherence factors may be use of a Fim-deficient UPEC mutant.…”
Section: Discussionsupporting
confidence: 80%
“…Coordinate regulation among fimbrial operons has been described previously and may provide an explanation for this observation (17,44). P fimbriae, argued as being virulence factors during UTI (43), are found downregulated here in vivo despite the presence of P-fimbrial Gal-Gal receptors in mice (22,32). Our microarray experiments suggest that a better way to study the importance of other adherence factors may be use of a Fim-deficient UPEC mutant.…”
Section: Discussionsupporting
confidence: 80%
“…Although others have assessed the interaction of E. coli strains and mouse bladder (1,5,8,21) or the development of cystitis and pyelonephritis following experimental challenge of mice or nonhuman primates with E. coli (16,31,32), this is the first study to assess differences between the uropathogenicities of pyelonephritis and cystitis strains of E. coli in an animal model of UTI. We chose to use the transurethrally challenged mouse model which was originally described by Hagberg et al (9), who documented that a P-fimbria-expressing strain colonized the kidney better than P-fimbria-negative strains.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and expression of pap genes is epidemiologically linked with pyelonephritis-causing E. coli strains (18), but the role of P fimbriae in virulence has not been well defined. Earlier studies in our laboratory found no difference in murine urinary tract colonization or histology when deletions were made in both copies of the pap operon in E. coli CFT073 (denoted as strain UPEC76) (26) despite the presence of P fimbrial receptors in mice (19,29). However, it has been argued that this adhesin represents a virulence factor in other UTI studies (35,53).…”
mentioning
confidence: 85%